2007
DOI: 10.1158/1055-9965.epi-06-0605
|View full text |Cite
|
Sign up to set email alerts
|

Polymorphisms of Catechol-O-Methyltransferase in Men with Renal Cell Cancer

Abstract: The estrogen metabolite, 4-hydroxy-estrogen, has been shown to play a role in malignant transformation of male kidneys. To counteract the effects of this catechol-estrogen, the catechol-O-methyltransferase (COMT) enzyme is capable of neutralizing the genotoxic effects of this compound. A polymorphic variant of COMT has been shown to have a reduced enzyme activity, and thus, we hypothesize that single nucleotide polymorphisms of the COMT gene can be a risk factor for renal cell cancer (RCC). To determine this h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
14
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 20 publications
(16 citation statements)
references
References 42 publications
2
14
0
Order By: Relevance
“…Among other cancers including prostate, renal, lung, colorectal, and ovarian cancers, this codon 62 SNP studies have been examined [14,15,21]. Tanaka et al [14,15] reported the increased frequency of the codon 62 T/T genotype in prostatic and renal cell cancers, which is consistent with our results. The most widely studied polymorphic site in COMT gene is codon 158 and several studies have focused on the codon 158 polymorphism in the COMT gene in various carcinomas.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Among other cancers including prostate, renal, lung, colorectal, and ovarian cancers, this codon 62 SNP studies have been examined [14,15,21]. Tanaka et al [14,15] reported the increased frequency of the codon 62 T/T genotype in prostatic and renal cell cancers, which is consistent with our results. The most widely studied polymorphic site in COMT gene is codon 158 and several studies have focused on the codon 158 polymorphism in the COMT gene in various carcinomas.…”
Section: Discussionsupporting
confidence: 90%
“…Therefore the COMT Met variant allele may increase EC risk. A number of various cancer studies have focused on the codon 158 polymorphism in the COMT gene, but there are few studies that have investigated other polymorphic sites [14][15][16][17]. We have previously investigated other COMT SNPs including codons 62 (rs4633) and 72 (rs6267) in prostate and renal cancers in Japanese populations [14,15].…”
Section: Introductionmentioning
confidence: 99%
“…The most of the COMT occurring in human tissues is cytoplasmic [6,8,10,15,16]. However, COMT enzyme is polymorphic and its activity has significant differences among individuals [8, [14][15][16][17][18][19][20]. The single nucleotide polymorphism (SNP) G>A (rs4680) leads to an amino acid change of Val to Met in the position 108/158 in cytoplasmic/ membranous enzyme form, Submit your Manuscript | www.austinpublishinggroup.com respectively, and is generally known as Val158Met.…”
Section: Discussionmentioning
confidence: 99%
“…The single nucleotide polymorphism (SNP) G>A (rs4680) leads to an amino acid change of Val to Met in the position 108/158 in cytoplasmic/ membranous enzyme form, Submit your Manuscript | www.austinpublishinggroup.com respectively, and is generally known as Val158Met. This SNP has important (two-to fivefold) impact on the enzymatic activity as those individuals homozygous for the Val (GG) have high activity enzyme variant, those with Met/Met (AA) possess low activity protein and heterozygous genotype carriers (Val/Met, GA) have the enzyme form with intermediate activity [7,12,14,17,[19][20][21][22][23][24][25][26][27][28]. It means that alteration in the respective genotype leads to the change in efficacy of O-methylation of different endogenous and exogenous catecholic compounds (including for example catechol estrogens, but also flavonoids like quercetin, fisetin and different flavanols) and therefore also to the increased amounts of circulating catechols with significantly different bioactivities compared to their O-methylated metabolites.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation